(untitled) (REMUNOM, 2026)
This study reviews the specialized literature on management accounting, highlighting its relevance as a strategic tool for supporting organizational management. The research, bibliographic in nature and using a qualitative approach, brought together theoretical and practical contributions that allow us to understand the historical evolution of accounting, from its empirical origins to its consolidation as a social science. It is noteworthy that, although traditional accounting and management accounting share common foundations, they differ in objectives and target audiences: while the former prioritizes external users and legal compliance, the latter focuses on providing accurate and analytical information to managers. The review highlighted that management accounting operates along three central axes: planning, control, and decision-making, transforming data into useful information for improving organizational performance and the sustainability of operations. The conclusion is that management accounting transcends the merely technical or bureaucratic function of accounting, constituting an indispensable resource for strengthening information transparency. In this sense, its role as an applied social science is reaffirmed, capable of articulating theory and practice for the benefit of organizational efficiency and responsibility.